Cut protective materials from the point of view of working environment - Kropidłowska, Paulina; Irzmańska, Emilia; Andziński, Radosław (Wydawnictwo Politechniki Łódzkiej, 2022)
Cut resistance is defined as the ability of material to resist a blade, which may be determined by means of a variety and evaluation methods, depending on the intended use of the material and the applied cutting factor. Some of the earliest studies on cutting were conducted in the 1990s involving textile and polymeric materials. The obtained results were characterized by exponential regression indicating that blade movement (the length of the cutting path) decreases with increasing loading. Those results were reflected in the first version of the international standards specifying cut resistance testing [1–2]. Cut resistance tests given in international standards are mostly used for proving that products meet specific normative requirements, but they fail to account for the complexity of the physics of cutting and fall short in terms of evaluating advanced materials arising with the fast-paced development of materials technologies [3]. Moreover, the available literature does not contain many research on the cut resistance properties of e.g. three-dimensional hybrid textile materials taking into account the real conditions of use. As a result, it is need to develop more objective methods for evaluating cut resistance properties, therefore preliminary assumptions for the new method has been described in this paper.
Keywords: cut resistance; protective gloves; non-standard test methods; odporność na przecięcie; rękawice ochronne; niestandardowe metody badań